Sleep Disorders and Mood in Sports Students - Salsa Muzdalipa; Mohammad Zaky; Jajat; Yati Ruhayati (Universitas Negeri Semarang, 2025)
This study aims to determine the relationship between sleep disturbances and mood swings in sports students. Sleep disturbances are known to affect cognitive function, physical performance, and an individual's psychological state, particularly in adolescents undergoing developmental transitions. The study employed a quantitative approach with a cross-sectional design, involving 50 students majoring in Sports Science at the Indonesian University of Education, consisting of 27 males and 23 females aged 19–20 years. The instruments used included the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality and the Brunel Mood Scale (BRUMS) to assess mood. Data analysis was performed using a correlation test using SPSS version 26. The results showed that the majority of respondents experienced negative moods (78.6%), with tension and fatigue items being the most dominant. However, no significant relationship was found between sleep quality and mood swings (p > 0.05). This finding indicates that other factors such as lifestyle, academic stress, and social environment have the potential to have a greater influence on the mood of sports students. Further research with a larger sample size is recommended to deepen the understanding of the relationship between sleep disturbances and students' psychological state.